(untitled) (Research, Society and Development, 2021)
The best treatment for children who should be lived, with the best interests for the sustainability of human life. In handling criminal cases, the restorative justice approach provides different views and approaches to studying and dealing with a criminal act for the handling of restorative justice, that criminal acts are essentially from the viewpoint of criminal law in general, namely attacks on individuals and society as well as community relations. In restorative justice, it can also be found that the features of the formulation of justice are related to rights, judged by results. This meaning has brought a paradigm shift in understanding the concept of providing justice that is in the criminal justice system, it’s said that because in the concept of the criminal justice system in general, justice is considered to have been achieved, the value of the perpetrator can be sanctioned by the state and the victim doesn’t have a place in the settlement process, meanwhile. In the concept of a framework of restorative justice, perpetrators of criminal acts, victims and the whole community are involved in resolving criminal acts directly and focusing on recovery suffered by victims, while the state functions as a facilitator in the process of resolving criminal acts.